How Local Peoples Participating in Village Development Planning Process Case Study Wangkapi Sub-district, Mueang Uttaradit District, Uttaradit Province - Chanrungrueang, Mongkhon; Bodeerat , Chot; Phongrod, Yuvadee (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study the level of public participation in the formulation of village development plans, 2) to compare personal factors that affect public participation in the formulation of village development plans, and 3) Explore guidelines for promoting public participation in the formulation of village development plans in Wang Kaphi Subdistrict, Mueang Uttaradit District, Uttaradit Province. This is a mixed-method research, combining both quantitative and qualitative approaches. The quantitative part uses a sample size of 400 people, determined by Taro Yamane’s formula. The research tool is a questionnaire. Data were analyzed using descriptive statistics and inferential statistics, including frequency distribution, percentage, mean, standard deviation, and T-test and F-test statistics. For the qualitative research, data were collected from 10 key informants selected through purposive sampling using in-depth interviews. The information was then analyzed using content analysis and summarized in narrative form. The research results found that: 1. The overall level of public participation in the formulation of village development plans in Wang Kaphi Subdistrict is at a moderate level. When analyzed by aspect, the highest average score was in the aspect of benefit-receiving participation, while the lowest was in operational participation. This reflects the importance of engaging the public in all stages of the planning process, aligning with their real problems and needs. 2. In comparing levels of public participation based on personal factors, it was found that age, education level, occupation, and income showed statistically significant differences in opinions across four aspects of participation. However, gender and duration of residence did not show significant differences, at a 0.05 significance level. 3. Suggestions and guidelines for enhancing public participation include providing opportunities for people to participate in meetings and public hearings, promoting education and training, building networks between citizens and local agencies, encouraging collaboration in plan formulation, and establishing systems for monitoring and evaluation. These strategies are crucial for empowering citizens to play a key role in community development, thereby promoting sustainable village and subdistrict development in the long term.